Proposed Solutions to the Issues in Hiring and Promotion of Teachers and Principals - Frank Angelo Pacala (Indonesian Journal of Multidiciplinary Research, 2023)
This position paper looks at the moral dilemma in the school about students’ perceived success and teachers' and principals’ qualifications. The dilemma arises when an unlicensed teacher and non-principal test passer may lower the standard or level up the standard. This paper identified existing tensions and potential solutions to help mitigate conflict of interest scenarios. The paper begins with an overview of existing regulations and guidelines. It then discussed areas that were observed to have issues and problems including hiring staff, promoting employees, and ethics training programs. Finally, this paper recommended strategies for managing conflicts that are deemed necessary to address this ever-growing problem. The goal is to provide a comprehensive set of best practices that can be incorporated into organizations to ensure that hiring and promotion processes can lead to greater progress in the school and the community.